Development of E-Booklet Media to Improve Students’ Self-Regulated Learning - Sigit Dwi Sucipto; Rani Mega Putri; Silvia Ar (STAI Hubbulwathan Duri, 2022)
The purpose of this research is to develop a valid and practical self-regulated learning e-booklet. This study uses the ADDIE development model which has 5 stages (Tegeh, 2014) namely Analysis, Design, Development, Implementation, and Evaluation. Based on the results of research on the development of self-regulated learning E-Booklet media, it can be concluded that self-regulated learning E-Booklet media is prepared using the methods of analysis, planning, development and implementation. Then, the self-regulated learning E-Booklet Media is feasible to use and has a fairly high score in the validation results of the material test and display. The self-regulated learning E-Booklet media is effective in increasing student self-regulated learning and can be used as a medium for delivering information in the realm of guidance and counseling.